NAB2-STAT6融合遺伝子の同定により確定診断に至った口底部孤立性線維性腫瘍の１例 - 廣瀬, 勝俊; 古木, 良彦; 小野, 早和子; 中村, 友哉; 助川, 信太郎; 藤村, 愛 (日本口腔外科学会雑誌, 2024)
Solitary fibrous tumor (SFT) is an intermediate malignant tumor of the soft tissue. The specific fusion gene NAB2-STAT6 is detected in SFT. Although SFT occurs systemically, SFT of the oral floor is extremely rare. We report a case of SFT of the oral floor with NAB2-STAT6 fusion gene. A 54-year-old man had noticed a painless swelling in his oral floor for four years. Intraoral examination revealed a globular, wellcircumscribed, and elastic hard mass. Under a clinical diagnosis of benign tumor, the tumor was resected with the local anesthesia. Histological examination revealed the proliferation of spindle cells with branching vessels. RT-PCR confirmed the presence of the NAB2 exon4‒STAT6 exon2 fusion gene, and a diagnosis of SFT was made. There was no evidence of recurrence after one year and five months of follow-up.